Predicting Financial Distress in Indonesia's Retail Industry - Angela, Aurora; Oktavianti, Oktavianti; Tanison, Nindy (E-Jurnal Akuntansi; Vol 34 No 8 (2024)DO - 10.24843/EJA.2024.v34.i08.p13, 2024)
The condition of a healthy company is an ideal representation for all parties, both internal and external to the company. However, at times, there are moments when a company does not operate according to plan and may experience financial difficulties (financial distress). The threat of financial distress requires the company to have the appropriate strategy to anticipate conditions that may cause financial problems for the company. To predict financial distress, it can be analyzed from the financial ratios of the company. In this study, the researcher used operating capacity, profitability, leverage, and cash flow as independent variables and examined how they are related in predicting financial distress. The study used the entire population of retail sector companies in Indonesia with an observation period from 2019 to 2022. The retail sector was the focus of this research because in 2021, several retail sectors were in financial distress and even declared bankrupt. The conclusion of this research is that all four variables, namely operating capacity, profitability, leverage, and cash flow, have an effect in predicting financial distress. Operating capacity, profitability, and cash flow show a negative direction in their effect on predicting financial distress, while leverage shows a positive direction in its effect on financial distress. Keywords: financial distress, operating capacity, profitability, leverage, cash flow